ANALISIS BIBLIOMETRIKA KONTRIBUSI MUHAMMADIYAH SEBAGAI ORGANISASI DAKWAH DAN SOSIAL KEAGAMAAN (1995 - 2023) - Ahmadi, Ahmadi; Fattah, Mohammad; Supriyadi, Supriyadi (Bayan lin-Naas : Jurnal Dakwah Islam, 2024)
Since 2010, Muhammadiyah has entered the second century after its founding. Its existence has attracted researchers to discuss it in various aspects. This research aims to describe which journals, authors, affiliations and countries contribute to the study of Muhammadiyah. Then how studies on Muhammadiyah build upon each other from 1995 to 2023.This research uses bibliometric analysis, by analysing 923 documents indexed by Scopus with the keyword Muhammadiyah. Data processing and analysis used biblioshiny applications run through R and R-Studio applications.The research found that within 28 years, from 1995 - 2023, there were 2294 authors, 164 single authors, 6.609% international authorship collaboration, and 26703 references with an average citation per document of 3,243 citations related to Muhammadiyah. Academics who study are not only from Indonesia and internal Muhammadiyah universities, but also from various countries in the world.There are five Scopus indexed journals and proceedings that publish many studies on Muhammadiyah, namely: Journal of Physics: Conference Series, AIP Conference Proceedings, IOP Conference Series: Earth and Environmental Science, International Journal of Scientific and Technology Research, and Studia Islamika.Based on the results of bibliometric analysis, the trending topics are student, learning and school. Future research on Muhammadiyah can be used as a reference to discuss titles related to the words Muhammadiyah, Indonesia and Islamic. This trend is in accordance with Muhammadiyah's existence as a da'wah and social religious organization that wants to develop Islamic values in Indonesia in a widespread and sustainable manner.